New economic geography of market potential: Innovation intensity and labor structure in EU regions - Raine Hermans (The Research Institute of the Finnish Economy (ETLA), 2003)
In the present study, we ask how economic integration affects the location of economic activities, and spatial distribution of market potential, in Europe. The theoretical framework is based on the new economic geography approach in trade analysis literature. Empirical analysis transforms data into a synthetic free trade area (SFTA) that is constructed by standardizing the values of each variable to a comparable level in each country. Then SFTA is compared with the real trade area (RTA). The comparison offers insights into how “extreme” integration within countries (SFTA) has affected the location of economic activities and how this integration differs from the spatial structures among countries (RTA). The empirical results suggest that regional innovation intensity has affected the spatial market potential within countries but not among the same countries. This has important implications for the discussion about regional development during the economic integration process. The results imply that if international integration gets forms similar to those that “extreme” integration has had within countries, lower international trade barriers will lead to geographic concentration in the region with high innovation intensity. The conclusions of the results change in some respects when we use different data subgroups. Innovation intensity does not seem to be a relevant driver in all the subgroups formed. However, the labor share of agriculture remains a powerful predictor of geographical concentration in all the subsets and models.
Keywords: 330; economic integration; location; monopolistic competition; sunk costs; trade; Regionaler Arbeitsmarkt; Innovation; Wirtschaftsintegration; Regionale Konzentration; EU-Staaten; Marktpotential